PENERAPAN SISTEM PENDUKUNG KEPUTUSAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) REKOMENDASI SISWA BERPRESTASI UNTUK DIAJUKAN KE KELAS UNGGULAN - Wahyu Saputro, Angga; Rahman Prehanto, Dedy; Andriani, Anita (Inovate, 2019)
Madrasah tsanawiyah negeri is an islamic school which have the same level as junior high school.Sometimes it requires outstanding students to be recommended to a special class, which not only considersacademic score, but also non-academic of each student. To avoid subjective decision, it need DecisionSupport System (DSS) in providing student recommendations.One of DSS methods to solving a problem is TOPSIS. TOPSIS is based on the concept that the chosenalternative should have the shortest distance from the positive ideal solution as well as the longest distancefrom the negative ideal solutionThis study focuses on providing recommendation of outstanding students at MTsN TambakberasJombang. Observations data are collected from students grade 7 and processed using TOPSIS method. Thecriteria variables are academic score, nonacademic score, extra score, attitude score, attendance score,communication skill, and expertness. The result of preference score is generated by system then comparedwith result of manual. The comparison obtained an accuracy of 99.75%. Then, based on blackbox testingit can be concluded that the system is feasible to be used in this study case.Keywords: DSS, TOPSIS, Recommended Student, Outstanding Class.